Photovoltaic materials - Al-Bat’hi, Souad A. M. (2012)
Solar Cell, Photovoltaic Cell & photovoltaics A solar cell: is a device that converts the energy of sunlight directly into electricity by the photovoltaic effect. Sometimes the term solar cell is reserved for devices intended specifically to capture energy from sunlight, while the term photovoltaic cell is used when the light source is unspecified.